Exploring individual cognitions, self-regulation skills, and environmental-level factors as mediating variables of two versions of a Web-based computer-tailored nutrition education intervention aimed at adults: A randomized controlled trial. (1st March 2016) - Springvloet, Linda; Lechner, Lilian; Candel, Math J.J.M.; de Vries, Hein; Oenema, Anke
Abstract: Background: This study explored whether the determinants that were targeted in two versions of a Web-based computer-tailored nutrition education intervention mediated the effects on fruit, high-energy snack, and saturated fat intake among adults who did not comply with dietary guidelines. Method: A RCT was conducted with a basic (tailored intervention targeting individual cognitions and self-regulation), plus (additionally targeting environmental-level factors), and control group (generic nutrition information). Participants were recruited from the general Dutch adult population and randomly assigned to one of the study groups. Online self-reported questionnaires assessed dietary intake and potential mediating variables (behavior-specific cognitions, action- and coping planning, environmental-level factors) at baseline and one (T1) and four (T2) months post-intervention (i.e. four and seven months after baseline). The joint-significance test was used to establish mediating variables at different time points (T1-mediating variables – T2-intake; T1-mediating variables – T1-intake; T2-mediating variables – T2-intake). Educational differences were examined by testing interaction terms. Results: The effect of the plus version on fruit intake was mediated (T2–T2) by intention and fruit availability at home and for high-educated participants also by attitude. Among low/moderate-educated participants, high-energy snack availability at home mediated (T1–T1) the effect of the basic version on high-energy snack intake. Subjective norm mediated (T1–T1) the effect of the basic version on fat intake among high-educated participants. Discussion: Only some of the targeted determinants mediated the effects of both intervention versions on fruit, high-energy snack, and saturated fat intake. A possible reason for not finding a more pronounced pattern of mediating variables is that the educational content was tailored to individual characteristics and that participants only received feedback for relevant and not for all assessed mediating variables. Trial registration: Netherlands Trial Registry NTR3396. Highlights: Mediators of 2 computer-tailored nutrition education intervention versions were explored. Both versions were effective in changing some of the dietary outcomes. Some targeted determinants mediated the effects of both intervention versions. Some indications for educational differences in mediating variables were found.